PML promotes metastasis of triple-negative breast cancer through transcriptional regulation of HIF1A target genes - Manfredi Ponente; Letizia Campanini; Roberto Cuttano; Andrea Piunti; Giacomo A. Delledonne; Nadia Coltella; Roberta Valsecchi; Alessandra Villa; Ugo Cavallaro; Linda Pattini; Claudio Doglioni; Rosa Bernardi (JCI Insight, 2017)
Elucidating the molecular basis of tumor metastasis is pivotal for eradicating cancer-related mortality. Triple-negative breast cancer (TNBC) encompasses a class of aggressive tumors characterized by high rates of recurrence and metastasis, as well as poor overall survival. Here, we find that the promyelocytic leukemia protein PML exerts a prometastatic function in TNBC that can be targeted by arsenic trioxide. We found that, in TNBC patients, constitutive HIF1A activity induces high expression of PML, along with a number of HIF1A target genes that promote metastasis at multiple levels. Intriguingly, PML controls the expression of these genes by binding to their regulatory regions along with HIF1A. This mechanism is specific to TNBC cells and does not occur in other subtypes of breast cancer where PML and prometastatic HIF1A target genes are underexpressed. As a consequence, PML promotes cell migration, invasion, and metastasis in TNBC cell and mouse models. Notably, pharmacological inhibition of PML with arsenic trioxide, a PML-degrading agent used to treat promyelocytic leukemia patients, delays tumor growth, impairs TNBC metastasis, and cooperates with chemotherapy by preventing metastatic dissemination. In conclusion, we report identification of a prometastatic pathway in TNBC and suggest clinical development toward the use of arsenic trioxide for TNBC patients.